Neocoleroa metrosideri sp. nov. (Sympoventuriaceae, Venturiales) - Johnston, Peter R.; Park, Duckchul (Phytotaxa, 2016)
Neocoleroa metrosideri is described as a new species and phylogenetically it is shown to belong in the Sympoventuriaceae, a recently established family, sister to the Venturiaceae. No other sequences are available for Neocoleroa but this new species is morphologically typical of the type species, with distinctive lobed to dichotomously branched, blunt-tipped setae on the superficial pseudothecia. The genus has previously been placed in the Pseudoperisporiaceae. This leaf spotting fungus is known from only a single specimen in an urban park but the same fungus has been detected also from two natural forest sites as an OTU in 454-based high throughput amplicon sequencing from DNA extracted from living leaves of Metrosideros excelsa.